The design and development of Knowledge Map (K-Map) model in visualizing dengue outbreak area using remote sensing and GIS technique / Nazri Che Dom … [et al.] - Che Dom, Nazri; Abd Latif, Zulkiflee; Ismail, Rodziah; Mohd Yatim, Siti Rohana; Abd Rahman, Padma (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Dengue disease is one of the most rapidly spreading infectious diseases worldwide and up to now no immunization is available. This model used geographical information system (GIS) and remote sensing (RS) data to formulate a process for development of reference maps (K-Map) in visualizing the dengue hotspot in a locality. The methodology used in the study and the result obtained could be useful for documentation by epidemiologist for active surveillance and thus help to reduce dengue outbreak in a locality. This model integrates the environmental indicator and the epidemiological component to derive a quantitative spatial model on urban environment. Hence this model offers a simple, inexpensive technique for early warning, categorization and identification of a locality for surveillance, monitoring and evaluation of dengue outbreak.